Al-Tashbīh wa Al-Tajsīm fī al-Fikr al-Kalāmī al-Islāmī Ru'yah Taḥlīliyyah li Adillah Al-Mujassimah fī Ḍaw' Mu'taqid Ahl Al-Sunnah wa Al-Jama'ah - RifÄâ€™Ä«, Muá¸¥ammad (Jurnal Usuluddin, 2009)
Ma`rifat Allah (gnosis of God) is compulsory for all human being in order to achieve happiness in this world and hereafter. Allah S.W.T. commands human being to know Him through His saying, means: â€œSo know that there is no God (worthy of worship) except Allah.â€ The Prophet p.b.u.h. also ordered them to be sincere in their devotion and they have not been asked to know Allah S.W.T. through His Dhat, but only by the means of His perfect Attributes. However, there are people who seek the reality of His Dhat and they used certain texts (nass) together with their imaginations and scepticism to represent Allah as similar to His own creation. The faith of early Muslims generations were pure, until they were influenced by the notions of â€œtashbihâ€ and â€œtajsimâ€ which came from the Jews and Christians teaching which is had been accepted by Shi`ah extremists. Furthermore, this kind of conception spread among the Ahl al-Sunnah wa al-Jama`ah. Adherents of this thought are called â€œal-Mujassimahâ€ and â€œal-Mushabbihah. As their belief was revived in the name of Ahl al-Sunnah wa al-Jama`ahs belief, so therefore this article would like to explain the attitudes of Ahl al-Sunnah towards this complex issues.